The Fish Family Poeciliidae as a Model to Study the Evolution and Diversification of Regenerative Capacity in Vertebrates - Safian, Diego; Wiegertjes, Geert F.; Pollux, Bart J. A. (Frontiers in Ecology and Evolution, 2021)
The capacity of regenerating a new structure after losing an old one is a major challenge in the animal kingdom. Fish have emerged as an interesting model to study regeneration due to their high and diverse regenerative capacity. To date, most efforts have focused on revealing the mechanisms underlying fin regeneration, but information on why and how this capacity evolves remains incomplete. Here, we propose the livebearing fish family Poeciliidae as a promising new model system to study the evolution of fin regeneration. First, we review the current state of knowledge on the evolution of regeneration in the animal kingdom, with a special emphasis on fish fins. Second, we summarize recent advances in our understanding of the mechanisms behind fin regeneration in fish. Third, we discuss potential evolutionary pressures that may modulate the regenerative capacity of fish fins and propose three new theories for how natural and sexual selection can lead to the evolution of fin regeneration: (1) sexually driven fin regeneration, (2) predation driven fin regeneration, and (3) life history driven fin regeneration. Finally, we argue that fish from the family Poeciliidae are an excellent model system to test these theories, because they comprise of a large variety of species in a well-defined phylogenetic framework that inhabit very different environments and display remarkable variation in reproductive traits, allowing for comparative studies of fin regeneration among closely related species, among populations within species or among individuals within populations. This new model system has the potential to shed new light on the underlying genetic and molecular mechanisms driving the evolution and diversification of regeneration in vertebrates.